PPM-18, an Analog of Vitamin K, Induces Autophagy and Apoptosis in Bladder Cancer Cells Through ROS and AMPK Signaling Pathways - Lu, Huiai; Mei, Chunlei; Yang, Luhao; Zheng, Junyan; Tong, Junwei; Duan, Fengsen; Liang, Huageng; Hong, Ling (Frontiers in Pharmacology, 2021)
PPM-18, identified as a novel analogue of Vitamin K, has been reported to play a critical role in the suppression of seizures. However, the concerns that whether PPM-18, like Vitamin K exerts anticancer activity remain to be further investigated. Here, we found that PPM-18 remarkably suppressed the proliferation, and induced apoptosis in bladder cancer cells. Furthermore, significant autophagic effect of PPM-18 on bladder cancer cells was also demonstrated, which profoundly promoted apoptotic cell death. Mechanistically, PPM-18 activated AMP-activated protein kinase (AMPK), whereas repressed PI3K/AKT and mTORC1 pathways in bladder cancer cells. Inhibition of AMPK markedly relieved PPM-18-induced autophagy and apoptosis, indicating that PPM-18 is able to induce autophagy and apoptosis in bladder cancer cells via AMPK activation. Moreover, reactive oxygen species (ROS) were notably accumulated in PPM-18-treated bladder cancer cells, and treatment with ROS scavengers, not only eliminated ROS production, but also abrogated AMPK activation, which eventually rescued bladder cancer cells from PPM-18-triggered autophagy and apoptotic cell death. In bladder cancer xenografts, the anticancer activities of PPM-18, including suppressing the growth of tumors and inducing autophagy and apoptosis in tumor cells, were also established. Collectively, this study was first to demonstrate the anticancer effect of PPM-18 on bladder cancer cells in vitro and in vivo through eliciting autophagy and apoptosis via ROS and AMPK pathways, which might provide new insight into the potential utilization of PPM-18 for future bladder cancer treatment.